Anestesi Umum pada Laparotomi dengan Indikasi Peritonitis Generalisata et causa Perforasi Apendisitis: Laporan Kasus - Made Sherly Armiyanti; Asep (CV. Jasa Sukses Abadi, 2023)
Peritonitis is inflammation of the peritoneal cavity. Secondary peritonitis is one of the most common fatal surgical emergencies with a 10%−60% morbidity and mortality rate. Appendicitis is a common cause of peritonitis with an estimated prevalence of approximately 43.1%. The patient's prognosis is influenced by several factors, one of which is the quality of treatment. Surgery performed by a surgeon will certainly result in a faster and more effective treatment. Patient An. A, 7 years old, came with complaints of very severe abdominal pain since 2 hours before admission to the hospital, felt like being stabbed. Initially abdominal pain is felt in the lower right side, after that it spreads to all parts of the stomach. The patient has a history of abdominal massage by a shaman 5 hours before admission to the hospital. On physical examination, there was fever, tachycardia, VAS score 8, there was abdominal distension, Mc Burney’s sign, abdominal tenderness, muscular defans and rebound tenderness. The results of laboratory tests showed leukocytosis, thrombocytosis, and electrolyte imbalance. The results of an abdominal ultrasound examination showed acute appendicitis with suspicion of perforation. The patient was diagnosed with generalized peritonitis e.c appendicitis perforated and planned to perform laparotomy + appendectomy under general anesthesia. The postoperative diagnosis of the patient was generalized peritonitis + intestinal adhesions + perforated appendicitis by laparotomy + adhesiolysis + appendectomy.